2023
DOI: 10.2217/fon-2022-0579
|View full text |Cite
|
Sign up to set email alerts
|

The value of pretreatment glucose-to-lymphocyte ratio for predicting survival of metastatic gastric cancer

Abstract: Aim: To demonstrate the prognostic importance of glucose-to-lymphocyte ratio (GLR) in metastatic gastric cancer (mGC). Methods: Retrospectively, 159 mGC patients were enrolled. Kaplan–Meier curve and Cox regression analysis were used to determine the prognostic value of the systemic immune inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), prognostic nutritional index (PNI) and GLR. Results: Progression-free survival (PFS) and overall survival (OS) were associated with NLR, PNI, SII and GLR by uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The Globulin-lymphocyte ratio (GLR) has been associated with poor prognosis in various cancer types including lung, breast, stomach, liver, esophageal, kidney, colorectal cancers, and melanoma, as evidenced by a study encompassing 2172 patients. 10 Similarly, Hannarici et al 13 for metastatic stomach cancer and Yang et al 12 for colorectal cancers have shown GLR to be an independent prognostic marker.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Globulin-lymphocyte ratio (GLR) has been associated with poor prognosis in various cancer types including lung, breast, stomach, liver, esophageal, kidney, colorectal cancers, and melanoma, as evidenced by a study encompassing 2172 patients. 10 Similarly, Hannarici et al 13 for metastatic stomach cancer and Yang et al 12 for colorectal cancers have shown GLR to be an independent prognostic marker.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is limited research on the use of GLR as a prognostic marker in pancreatic cancer. [10][11][12][13] This study aimed to investigate the impact of GLR on prognosis and survival in patients undergoing surgery for pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Yılmaz A and colleagues ( 17 ) have discovered that GLR prior to sorafenib therapy serves as a novel prognostic biomarker, accurately predicting survival rates in patients diagnosed with advanced hepatocellular carcinoma. The prognostic significance of the GLR has been demonstrated in studies involving metastatic gastric cancer (mGC) and metastatic breast cancer (MBC) patients receiving Cdk 4/6 inhibitors ( 16 ). Additionally, in patients with type 2 diabetes and MBC, the preoperative hyperglycemia to lymphocyte ratio was found to be an independent predictor of preoperative central lymph node metastasis ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated GLR may serve as an indicator of the combined impact of hyperglycemia and immune dysfunction in critically ill individuals. Current clinical studies suggest that elevated GLR is an important predictor of acute mortality and prognosis in patients with gastric cancer ( 16 ),hepatocellular carcinoma ( 17 ), breast cancer, thyroid cancer, rectal cancer ( 18 ), acute respiratory distress syndrome and acute exacerbation of chronic obstructive pulmonary disease ( 11 ).Therefore, it has important clinical significance in terms of malignant tumor disease burden and respiratory disease burden. The aim of this study was to evaluate the correlation between GLR at admission and prognosis of hospitalization in patients with non-traumatic cerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%